The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.3945/jn.116.232314
|View full text |Cite
|
Sign up to set email alerts
|

Combining Intensive Counseling by Frontline Workers with a Nationwide Mass Media Campaign Has Large Differential Impacts on Complementary Feeding Practices but Not on Child Growth: Results of a Cluster-Randomized Program Evaluation in Bangladesh

Abstract: Background: Complementary feeding (CF) contributes to child growth and development, but few CF programs are delivered at scale. Alive & Thrive addressed this in Bangladesh through intensified interpersonal counseling (IPC), mass media (MM), and community mobilization (CM).Objective: The objective was to evaluate the impact of providing IPC + MM + CM (intensive) compared with standard nutrition counseling + less intensive MM + CM (nonintensive) on CF practices and anthropometric measurements.Methods: We used a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
134
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 118 publications
(142 citation statements)
references
References 24 publications
8
134
0
Order By: Relevance
“…From an implementation perspective, community‐level interventions by trained community volunteers and health care workers have potential to reach vulnerable populations at scale. Intervention programmes such as those implemented by Alive and Thrive (Menon et al, ) and CARE (Owais et al, ) in Bangladesh that were delivered by trained community health and nutrition workers have been effective at improving CF practices in the intervention areas.…”
Section: Discussionmentioning
confidence: 99%
“…From an implementation perspective, community‐level interventions by trained community volunteers and health care workers have potential to reach vulnerable populations at scale. Intervention programmes such as those implemented by Alive and Thrive (Menon et al, ) and CARE (Owais et al, ) in Bangladesh that were delivered by trained community health and nutrition workers have been effective at improving CF practices in the intervention areas.…”
Section: Discussionmentioning
confidence: 99%
“…In Bangladesh, the intervention consisted of outreach-based home counseling delivered by a nongovernmental organization (15). In Ethiopia, the CF counseling was delivered by outreach-focused governmental health system workers (16).…”
Section: Introductionmentioning
confidence: 99%
“…Mass media (MM) and community mobilization (CM) were used in all 3 countries to complement interpersonal counseling (IPC). Thus far, these studies have shown varying, but positive, impacts on breastfeeding in all 3 contexts (16, 17) and on CF in Bangladesh and Ethiopia (15, 16). …”
Section: Introductionmentioning
confidence: 99%
“…This trend is consistent with data from the HIES which reported 9.8 kg/person/year 9 The endline survey for the Alive and Thrive study has since been published (Menon et al, 2016), however these more recent consumption patterns are linked to a behaviour change intervention and so are not discussed further here. The study did not include a control group.…”
Section: Fish Consumption In Bangladeshsupporting
confidence: 84%